Tamanho e secagem de sementes de palmeira Jussara sobre a germinação e o vigor - Martins, Cibele Chalita [UNESP]; Machado, Carla Gomes [UNESP]; Nakagawa, Joao [UNESP]; Costa de Oliveira, Silvia Sanielle (Univ Fed Rural Semi-arido-ufersa, 2009)
With the objective to determine the influence of the dehydration and of the size and/or weight on germination percentage and the vigor of jussara palm seeds (Euterpe edulis Mart.), 10 individuals' ripe fruits, picked in the Experimental Station of Ubatuba (IAC) they were classified by size in 5 sieves of circular sieve: 26/64" (10,31mm), 28/64" (11,11mm), 30/64" (11,90mm), 32/64" (12,69mm) and 34/64" (13,49mm). It was determined, the medium weight of the classified seeds. The quality of the seeds was evaluated through the following parameters: water content of the seeds; germination and vigor (first germination counting). It was evaluated the drying speed of different seed sizes for 48 hours, in dry chamber. The sizes of 28/64", 30/64" and 32/64" represented 98,7% of the total weight of the harvested seeds and showed similar drying speed, percentage of germination and vigor. With the increase of the drying period, the smaller seeds (28/64") had their germination less affected them the intermediate (30/64") and bigger sized seeds (32/64").

Com o objetivo de verificar a influência da desidratação e do tamanho e/ou peso sobre a porcentagem de germinação e o vigor de sementes de palmeira jussara (Euterpe edulis Mart.), frutos maduros de 10 indivíduos, colhidos na Estação Experimental de Ubatuba (IAC) foram classificados por tamanho em 5 peneiras de crivo circular: 26/64” (10,31mm), 28/64" (11,11mm), 30/64" (11,90mm), 32/64" (12,69mm) e 34/64" (13,49mm). Determinou-se, o peso médio das sementes classificadas. A qualidade das sementes foi avaliada através dos seguintes parâmetros: teor de água das sementes, germinação e vigor (primeira contagem de germinação). Foi avaliada a velocidade de secagem das sementes de tamanhos diferentes por 48 horas, em câmara seca. As sementes de tamanho 28/64", 30/64" e 32/64" representaram 98,7% do peso total das sementes colhidas e apresentaram similar velocidade de secagem, porcentagem de germinação e vigor. Com o aumento do período de secagem, as sementes menores (28/64") apresentaram a germinação menos prejudicada que as médias (30/64") e maiores (32/64").
Size and drying of Jussara palm seeds on the germination and vigor
Keywords: Euterpe edulis Mart.; size; drying; heart of palm